Polarization-induced electro resistance and magneto resistance in La0.67Ca0.33MnO3/BaTiO3 composite film. Issue 4 (March 2018) - Wu, Lei; Dong, Chunhui; Wang, Xiaoqiang; Wang, Boyu; Li, Jinsheng; Jiang, Changjun
Abstract: La0.67 Ca0.33 MnO3 /BaTiO3 composite films have been grown on Nb-doped SrTiO3 substrates by the sol–gel method. The magnetic and ferroelectric properties in the composite films are investigated. A three-state memory is formed by applying a vertical electric field across the La0.67 Ca0.33 MnO3 /BaTiO3 heterostructure, this behavior is attributed to the polarization-mediated resistive switching effect. In addition, the transport properties of La0.67 Ca0.33 MnO3 thin film can be modulated by an external magnetic field, a 10.3 K shift of the metal insulator transition temperature is obtained with the change of applied magnetic field from 0 T to 6 T. Consequently, in La0.67 Ca0.33 MnO3 /BaTiO3 heterostructure, the resistance behavior can be modulated by piezoelectric effect, ferroelectric polarization and magnetic field simultaneously.